Dual epigenetic modifiers for cancer therapy. (4th July 2017) - José-Enériz, Edurne San; Rabal, Obdulia; Agirre, Xabier; Oyarzabal, Julen; Prosper, Felipe
ABSTRACT: Epigenetic drug discovery is an emerging strategy for the treatment of cancer and other pathologies. Here, we discuss our recent discovery of first-in-class dual reversible inhibitors of the histone methyltransferase activity of G9a/EHMT2 and DNA methyltransferases showing in vivo efficacy in human tumors. Current and future investigation lines are presented.